Deletion 21q22.3 and duplication 7q35q36.3 in a Colombian girl: A case report (2016)
Genetic disorders are a major cause in the etiology of cases with intellectual disability; however, analysis by a conventional technique such as cytogenetic karyotyping only allows the detection of chromosomal alterations in approximately 9.5 % of cases. The inclusion of new technologies such as high resolution microarray analysis has allowed the study of alterations in chromosomal segments that are less than 5 Mb in length; this has led to an increase in the diagnosis of these patients of up to 25 %.